The Correlation Between Knowledge of Local Food Utilization and Clean, Healthy Living Behavior with Nutritional Status of Toddlers - Riska Agustina; Deisy Sri Hardini (UM Purwokerto Press, 2024)
Background: Nutritional status issues in toddlers are caused by insufficient food intake and diseases. The most important primary prevention effort involve various human activities and behaviors, including meeting nutritional needs and implementing the Clean Healthy Living Behavior program. Method: This study employed a quantitative approach with a Cross-sectional research design. The sample consisted of 74 mothers of toddlers aged 6-59 months in Panembangan Village, Cilongok District, Banyuma Regency, selected using the Sampling Fraction Per Cluster technique. Data were analyzed using the Chi-Square test. Results: The study found that the most dominant level of education was junior hight school (39,2%), and most mother were housewives (87,8%). Most parents in Panembangan Village had good knowladge of local food utilization (70,3%), and there was a significant correlation between parental knowladge and nutritional status, with Continuity Correction of 0.037. In terms of Clean, Healthy Living Behavior (CHLB), most respondents in Panembangan Village exhibited good behavior (94,6%), and there was a significant relationship between CHLB and the nutritional status of toddlers, with a Fisher’s Exact Test of 0,046. Conclusion: There is a correlation between knowledge of local food utilization and clean, healthy living behavior with nutritional status of toddlers.